2014
DOI: 10.3109/0886022x.2014.982489
|View full text |Cite
|
Sign up to set email alerts
|

Early markers of cardiovascular risk in chronic kidney disease

Abstract: Serum cardiac biomarkers and nontraditional cardiovascular risk factors increase already in the stage 2/3 KDOQI contributing to explain the high cardiovascular morbidity and mortality of these patients. The NT-proBNP seems to have a rise earlier compared with serum cTnT; however, both seemed to be a useful clinical biomarker for evaluating noninvasive predictors of atherosclerosis in CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Several studies have identified V’E/V’CO 2 , anaerobic threshold, and V’O 2max as prognostic factors in cardiovascular diseases [62-63]. We found, also, a significant increase of cTnT in ADPKD patients, a sensitive and specific marker of ischemic myocardial damage, renally cleared, and widely used as a predictor of cardiovascular events [53]. Our results indicate an increase of the indexes of inflammation and endothelial dysfunction, with reduced tolerance to stress and decreased anaerobic threshold to CPET, in young ADPKD patients, with preserved renal function, in the early stages of disease, compared to control group.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies have identified V’E/V’CO 2 , anaerobic threshold, and V’O 2max as prognostic factors in cardiovascular diseases [62-63]. We found, also, a significant increase of cTnT in ADPKD patients, a sensitive and specific marker of ischemic myocardial damage, renally cleared, and widely used as a predictor of cardiovascular events [53]. Our results indicate an increase of the indexes of inflammation and endothelial dysfunction, with reduced tolerance to stress and decreased anaerobic threshold to CPET, in young ADPKD patients, with preserved renal function, in the early stages of disease, compared to control group.…”
Section: Discussionmentioning
confidence: 76%
“…Patients with chronic kidney disease (CKD) have markedly increased rates of cardiovascular (Foley et al 1995;Lai et al 2015) and cerebrovascular disease (Dad and Weiner 2015) and mortality even before reaching end-stage renal disease (ESRD). Therefore, it is critical to identify early biomarkers predicting major adverse cardiovascular and cerebrovascular events (MACCEs) or survival in patients with CKD.…”
Section: Introductionmentioning
confidence: 99%
“…In these patients with early renal failure and activated coagulation system, prevalence of coronary heart disease, cerebrovascular disease, and peripheral arteriopathy was significantly higher than in patients with GFR of 90 mL/min per 1.72 m 2 or more and cardiovascular disease was independently predicted by both plasma D-dimer and fibrinogen levels. Consistently, in 50 patients with stage 2-3 renal failure plasma fibrinogen was significantly increased possibly contributing to the high cardiovascular morbidity of these patients [35] . In the 3758 patients with GFR of 20 to 70 mL/min per 1.72 m 2 of the Chronic Renal Insufficiency…”
Section: Non-traditional Cardiovascular Risk Factorsmentioning
confidence: 52%